Minimizing Dust in Low Rise Housing Design Through Surface: A Literature Review - Rizka Tiara Maharani; Sri Nastiti Nugrahani Ekasiwi; Franciscus Teddy Badai Samodra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
The existence of dust in a building environment can cause many problems for those who continually exposed, especially for residential housing which is located near the industrial area. There are so many kinds of dust included PM10 in which it can make upper respiratory tract infection. So, it needs a treatment process for reducing the dust intensity, one of the ways is through exploring the surface. In this paper highlighted about literature review for knowing the element surfaces that related to the way for reducing dust. Therefore, in this stage is needed for searching the surface elements that can be used in the next design process. The result of this review is the selection of building shape can help in controlling dust spread such as in courtyard typology. After that, it should consider with tilt angle of the surface in order to dust cannot be trapped and the position of surface from the direction of wind. The surface should have a minimum opening regarding to standard so that the view should face to the area where is not exposed by dust and air exchange can use shaft ventilation or hidden gap in the wall for helping to air flow.